Strategy of Implementation Supervision of Regional Head Elections 2020 In The Era of Pandemic Covid-19 In Kotabaru Regency - Fat Hurrahman; Andi Tenri Sompa; M Riduansah Syafari (International Journal of Politic, Public Policy and Environmental Issues, 2022)
The challenge that must be faced is the Covid-19 pandemic that is endemic throughout the world, including Indonesia. This condition had caused delays in voting in the Regional Head General Election in Kotabaru Regency. This study aimed to analyze the Supervision Strategy for the Implementation of Simultaneous Regional Head Elections in 2020 in the Covid-19 Pandemic Era in Kotabaru Regency, Indonesia. The strategy for supervising the implementation of the 2020 simultaneous regional head elections in the era of the COVID-19 pandemic in Regency Kotabaru has been carried out comprehensively and according to the rules. Specifically, Strategy Monitoring Bawaslu Kotabaru identification of problems in terms of US neutrality, to prevent either through electronic media in Kotabaru district, express or orally, giving advice or conveying information about the sanctions for violating ASN. In addition, the Kotabaru Regency Bawaslu also builds coordination with stakeholders and socialization participatory, coordination meetings with stakeholders and collects information on the health condition of each PPS member and monitors and consolidates the implementation of health protocols that are strictly implemented.